2018
DOI: 10.1007/s11356-018-3114-8
|View full text |Cite
|
Sign up to set email alerts
|

Lead exposure from households and school settings: influence of diet on blood lead levels

Abstract: Lead is known as a potent toxicant to human health, particularly for children while their central nervous system is developing. The aim of this study was to investigate the associations between blood lead levels (BLLs) and lead exposure in the children's diet, home, and school environments. A cross-sectional study was conducted with 153 children aged 1-4 years, in four day care centers (DCCs), where a high prevalence of lead exposure was previously found. Lead determination by graphite furnace atomic absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Other hygiene and personal care products can also be a source of PTE exposure [52], adding to the risks estimated in the present study. Moreover, other sources unrelated to cosmetics may contribute to PTE exposure, such as toys, playground paints, diet, and occupational activities [55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Other hygiene and personal care products can also be a source of PTE exposure [52], adding to the risks estimated in the present study. Moreover, other sources unrelated to cosmetics may contribute to PTE exposure, such as toys, playground paints, diet, and occupational activities [55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that cases spend time in places other than the home, especially for school-aged children. A study in Sao Paulo, Brazil, found no associations with lead intake by diet (p = 0.4) or mean lead found in household environmental screenings (p = 0.15) but did find an association with day care centres environmental screenings (p < 0.001) [54], suggesting that settings other than the home are important for lead exposure and need to be considered for case investigation. Time spent in education and day care settings should also be considered for exposure to lead sources and is considered in UK public health risk assessments.…”
Section: Limitationsmentioning
confidence: 92%
“…Further exposures which may be associated with elevated BLC were not included in our analyses and may therefore give rise to residual confounding; for example, housing tenancy (owned or rented) [18,51] parental occupation [52,53], ethnicity [17], other sources of exposure, diet, contaminated land, soil quality or contaminated consumer products [6,19,20,38,41,54]. Additionally, some case characteristics used ecological proxy measures based on area (e.g., deprivation, housing age and type) which may be inaccurate, leading to misclassification.…”
Section: Limitationsmentioning
confidence: 99%
“…Qualitative analysis is an unbeatable feature of EDXRF due to its multielemental capability and the possibility to perform solid analysis with a minimum sample treatment. In this view, screening analysis is a seamless application for EDXRF, even more due to the widespread use of portable XRF systems (Leroux et al, 2018;McComb et al, 2014;Peng et al, 2020;Turner et al, 2015). However, some of the limitations of XRF in this domain are the limited sensitivity for some environmental-relevant elements and also overlapping issues of some characteristic X-ray lines (eg.…”
Section: Qualitative and Quantitative X-ray Fluorescence Analysismentioning
confidence: 99%